IDENTIFIKASI BAKTERI ECOLI PADA IKAN KEMBUNG (RASTRELLIGER) DENGAN MENAMBAH BIAKAN MURNI ATCC 25922 - Radhi Favianajla Yulianto; Devi Faustine Elvina Nuryadin; Wawan Wartono Wartono; Tedy Adywangsa Adywangsa (Universitas Muhammadiyah Gresik, 2024)
This study aims to identify escherechia coli (E. coli) bacteria in mackerel sold in traditional markets using pure breeding. This study was conducted at the Microbiology Laboratory of the UPTD for Testing and Implementation of Fishery Product Quality in July-August. The methods used include prediction tests, confirmation tests and biochemical tests. The results showed that mackerel (Rastrelliger) purchased in the market contained E. coli bacteria >1100APM/g which will have an impact on human health if consumed continuously which causes poor fish quality.